The orphan nuclear receptor, COUP-TF II, inhibits myogenesis by post-transcriptional regulation of MyoD function: COUP-TF II directly interacts with p300 and myoD. - Bailey, P (1998)
COUP-TF II is an orphan nuclear receptor that has no known ligand in the 'classical sense'. COUP-TF interacts with the corepressors N-CoR, SMRT and RIP13, and silences transcription by active repression and trans-repression. Forced expression of the orphan nuclear receptor COUP-TF II in mouse C2 myogenic cells has been demonstrated to inhibit morphological differentiation, and to repress the expression of: (i) the myoD gene family which encodes myogenic basic helix-loop-helix (bHLH) proteins; and (ii) the cell cycle regulator, p21(Waf-1/Cip-1). In the present study, we show that COUP-TF II efficiently inhibits the myoD -mediated myogenic conversion of pluripotential C3H10T1/2 cells by post-transcriptional mechanisms. Furthermore, repression of MyoD-dependent transcription by COUP-TF II occurs in the absence of the nuclear receptor cognate binding motif. The inhibition of MyoD-mediated trans-activation involves the direct binding of the DNA binding domain/C-region and hinge/D-regions [i.e. amino acid (aa) residues 78-213] of COUP-TF II to the N-terminal activation domain of MyoD. Over-expression of the cofactor p300, which functions as a coactivator of myoD-mediated transcription, alleviated repression by COUP-TF II. Further binding analysis demonstrated that COUP-TF II interacted with the N-terminal 149 aa residues of p300 which encoded the receptor interaction domain of the coactivator. Finally we observed that COUP-TF II, MyoD and p300 interact in a competitive manner, and that increasing amounts of COUP-TF II have the ability to reduce the interaction between myoD and p300 invitro. The experiments presented herein suggest thatCOUP-TF II post-transcriptionally regulates myoD activity/function, and that crosstalk between orphan nuclear receptors and the myogenic bHLH proteins has functional consequences for differentiation.